A theory of economic development - Landais, Bernard (DEMO, 2021)
Many societies are stuck in development ; to relaunch the process, the article proposes a new theoretical context derived from the MIE-Growth model extended to deve- lopment. The importance of human cultures and their transmission is emphasized, alongside all the more traditional forces of investment. Development is also considerably hampered and sociologically constrained by the existence of pressures on the choices of individuals.(original abstract)